Genetic parameters for weight, morphometry and oviposition of Africanized honeybee queens using simulated data - Martins, E. H. [UNESP]; Taroco, G.; Rovadoscki, G. A.; Oliveira, M. H. V. [UNESP]; Mourao, G. B.; Santos, D. M. B.; Brighenti, C. R. G.; Assis, T. L. O.; Nogueira, J. P. S.; Gaya, L. G. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2020)
This study aimed to estimate genetic parameters for simulated data of body weight (BW), abdominal width (AW), abdominal length (AL), and oviposition. Simulation was performed based on real data collected at apiaries in the region of Campo das Vertentes, Minas Gerais, Brazil. Genetic evaluations were performed using singleand two-trait models and (co)variance components were estimated by the restricted maximum likelihood method. The heritability for BW, AW, AL and oviposition were 0.54, 0.47, 0.31 and 0.66, respectively. Positive genetic correlations of high magnitude were obtained between BW and AW (0.80), BW and oviposition (0.69), AW and oviposition (0.82), and AL and oviposition (0.96). The genetic correlations between BW and AL (0.11) and between AW and AL (0.26) were considered moderate and low. In contrast, the phenotypic correlations were positive and high between BW and AW (0.97), BW and AL (0.96), and AW and AL (0.98). Phenotypic correlations of low magnitude and close to zero were obtained for oviposition with AL (0.02), AW (-0.02), and BW (-0.03). New studies involving these characteristics should be conducted on populations with biological data in order to evaluate the impact of selection on traits of economic interest.
Keywords: Apis mellifera; correlation; heritability; selection